Pemberdayaan Anak Yatim Melalui Pendayagunaan Dana ZIS (Zakat Infaq Sadaqah) Pada LAZ Washal - Efni Yulia Santri Harahap; Siti Aisyah (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2024)
In this study aims to determine the role of utilization of zakat, infaq and Sadaqah in the empowerment of orphans in the institution of amil zakat Al-Wasliyah Medan. This research was conducted by qualitative descriptive method. This study uses two types of data namely primary data and secondary data collected using interviews and literature studies. This study found that the utilization of zakat, infaq and Sadaqah funds has a role in empowering orphans through the distribution of 1000 Orphan packages. The distribution of ZIS funds carried out by LAZ Washal is the distribution of ZIS funds in a consumptive form. This distribution is given to mustahiq directly in the form of momentary assistance.